A Stackelberg game based two-stage framework to make decisions of freight rate for container shipping lines in the emerging blockchain-based market. (May 2021) - Zhong, Huiling; Zhang, Fa; Gu, Yimiao
Highlights: This paper developed a two-stage framework to study how shipping lines make decisions in the emerging blockchain-based market. The first finding is that entering into the emerging shipping blockchain can be both an opportunity and a challenge for shipping lines. The second finding is that the ability of filtering function in the low freight rate of shipping blockchain plays a key role in regulating the freight rate and preventing the price war in the container shipping market. Abstract: To improve the operational efficiency, blockchain technology has been gradually applied into the container shipping industry. As an easier, faster, more efficient platform, blockchain can help to enhance efficiency through digitalizing and easing paperwork. That means, blockchain will make the container shipping market more transparent. Changes in market characteristics will bring a significant problem, how will container shipping lines make decisions in the emerging blockchain-based market? This paper developed a Stackelberg game based two-stage framework to solve the problems. The first stage describes the process of container shipping lines deciding whether to enter the blockchain or not. The second stage describes how container shipping lines decide freight rate in an emerging blockchain-based market. The Cournot game and Stackelberg game are used to solve the second stage model. Spread factor is introduced to reflect the influence of the initial strategy on blockchain strategy. The classical demand function is modified to distinguish the non-blockchain market with more gentle competition from the blockchain market with more intense competition. Numerical experiment is applied to testify this paper. Results show: (1) Entering into the emerging shipping blockchain can be both an opportunity and a challenge for container shipping lines. (2) The ability of filtering function in the low freight rate of shipping blockchain plays a key role in regulating the freight rate and preventing the price war. This paper can provide decision suggestions for shipping lines at the early stage of blockchain introduction.